Sensory Profile of Children and Adolescents with Autism Spectrum Disorder and Tip-Toe Behavior: Results of an Observational Pilot Study - Giulio Valagussa; Giulia Purpura; Alessandra Nale; Rita Pirovano; Miryam Mazzucchelli; Enzo Grossi; Cecilia Perin (MDPI AG, 2022)
Atypical sensory processing is frequently reported in persons with autism spectrum disorders (ASD), and it is one of the described diagnostic criteria for ASD. There is also mounting literature supporting the presence of motor impairments in individuals with ASD. Among these motor signs, tip-toe behavior (TTB) is a possible clinical finding, but its etiology is not clearly understood. It is suggested that TTB in ASD could be a sign of a sensory modulation impairment, but evidence is lacking and controversial. The main aim of this pilot study is to explore sensory features in a sample (4 females; 28 males) of children and adolescents with ASD (age range: 7-18). All participants also presented Intellectual Disability. Participants were divided in two groups, matched for age and gender, on the basis of the presence or absence of TTB (16 ASD TTB group vs. 16 ASD NO-TTB group) and then evaluated by using the Short Sensory Profile. We found that both ASD groups tend to significantly present sensory-related behavioral symptoms, but ASD TTB individuals more frequently showed the specific pattern of "under responsive/seeks sensation" than ASD NO-TTB individuals. These preliminary findings support that sensory-motor features might be taken into consideration when rehabilitation for TTB in children and adolescents with ASD is necessary.